1988
DOI: 10.1161/01.str.19.8.942
|View full text |Cite
|
Sign up to set email alerts
|

Results of the seven-year prospective study of stroke patients.

Abstract: Using the registry method, 1,538 stroke patients were detected in one district of Moscow between January 1, 1972, and December 31, 1974. Of the 965 patients who survived the acute stage of stroke (the first 3 weeks after onset), 941 (505 women and 436 men) were followed for the next 7 years. We analyzed incidence and types of recurrent strokes. During this 7-year follow-up, we recorded 32.1% of the patients as having recurrent strokes, most of which developed in the first 3 years and especially during the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
3
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(88 citation statements)
references
References 8 publications
5
77
3
3
Order By: Relevance
“…[17][18][19] For cerebrovascular disease, previous studies also suggested that stroke recurrence, TIA, or myocardial infarction after a stroke reflects the progression of underlying vascular disease. 20,21 It is important to point out that the second TCD in the present study was performed after the onset of a recurrent event, if any. Therefore, we consider the progression of the MCA lesion to serve as a marker of the progression of the generalized atherosclerosis process.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] For cerebrovascular disease, previous studies also suggested that stroke recurrence, TIA, or myocardial infarction after a stroke reflects the progression of underlying vascular disease. 20,21 It is important to point out that the second TCD in the present study was performed after the onset of a recurrent event, if any. Therefore, we consider the progression of the MCA lesion to serve as a marker of the progression of the generalized atherosclerosis process.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the determinants and probabilities of survival and at various times after the index stroke have included all strokes, 3 first stroke, 4 -6 or ischemic stroke, [7][8][9][10] with emphasis on stroke subtype, 11 age, 12 or place of management. 13 The absolute risk for death after a stroke is an appropriate variable in analyses of prognostic factors, but the inferences to be drawn from the absolute survival probability may be limited because most stroke patients were in their 70s or 80s.…”
mentioning
confidence: 99%
“…The risk of vascular disorders in the central nervous system is increased by 6-25% per 1 mmol / l of the increased total cholesterol, and twice in the case of diabetes [18,20]. Schmidt and co-authors have indicated that the risk of the reoccurrence of stroke within the period of 7 years after the first episode, takes place in 28% of patients, a second relapse within the same period relates to 3% of patients and the third one to 0.6% of patients [21].…”
Section: Discussionmentioning
confidence: 99%